Trends and Determinants of Family Planning Utilization Among Men in Indonesia - Idris, Haerawati; Syafriyanti, Willyana (Makara Journal of Health Research, 2021)
Background: Population growth rate in the world is still increasing. To control population growth, governments issue family planning programs for married women and men. However, contraception use is still dominated by women. This study aims to analyze the trends and determinants of family planning utilization among men in Indonesia. Methods: This study is quantitative in nature with a cross-sectional design, using secondary data from the Indonesian Health Demographic Survey (2007–2017). The sample comprised married men with a total of 27,859 respondents. For the final analysis, we conducted logistic regression statistical tests to determine family planning utilization among men. Results: Family planning utilization trends among married men in Indonesia increased. The proportion utilization of family planning among men was 3.7% (2007), 4.2% (2012), and 5.6% (2017). Higher and secondary education, media exposure, age, type of residence, and economic status significantly correlated with family planning utilization among married men. Higher education was the most dominant factor associated with family planning utilization among males in Indonesia (p < 0.001; Prevalence Ratio (PR) 4.636 Confidence Interval 95% (3.645–5.897). Conclusions: Male education is the most crucial factor of family planning utilization. Increasing knowledge regarding family planning is expected to increase information and awareness about family planning utilization.